Penerapan Simple Water Filter pada Masyarakat Desa Benua Raya, Kecamatan Bati-Bati, Kabupaten Tanah Laut - Ramadhan, Hafiz; Forestryana, Dyera; Hasymi, Liana Fitriani; Sutomo, Sutomo; Khairunnisa, Amalia; Istikowati, Wiwin Tyas (Penerbit Goodwood, 2025)
Purpose: The aim of this community service is a form of disaster preparedness to prevent health problems through the implementation of simple water filters in Benua Raya Village, Bati-Bati District, Tanah Laut Regency. Methodology: Activities were carried out by implementing Clean and Healthy Living Behavior (PHBS) counseling and training on making simple water filters for community mothers and Posyandu cadres with a total of 52 people on September 18th, 2024. Results: The activity results showed that participants knew and understood the importance of PHBS, especially using clean and suitable water for daily life and when affected by natural disasters as a form of disease prevention. The percentage of knowledge before the activity was 80.77%-94.23%, which increased after the activity to 96.15%-100%. The level of knowledge and skills of participants in making simple water filters also increased from 44.23%-48.08% to 88.46%-94.23%. Conclusions: This activity concludes that counseling and training on making simple water filters can increase the awareness of the people of Benua Raya Village to implement PHBS and can be one of the family preparedness efforts in obtaining clean water when a flood disaster occurs. Limitations: The activity was only attended by Posyandu cadres and housewives. Contribution: The counseling, education, and training activities for the Benua Raya Village community need to be carried out consistently because they contribute to increased awareness of Clean and Healthy Living Behavior.